Exposing inequities in deep-sea exploration and research: results of the 2022 Global Deep-Sea Capacity Assessment - Katherine Lynn Croff Bell; Maud Caroline Quinzin; Diva Amon; Susan Poulton; Alexis Hope; Otmane Sarti; Titus Espedido Cañete; Alanna Matamaru Smith; Harriet Isobel Baldwin; Drew Marie Lira; Sergio Cambronero-Solano; Tyler-Rae Aiysha Chung; et al. (Frontiers in Marine Science, 2023)
The 2022 Global Deep-Sea Capacity Assessment is a baseline assessment of the technical and human capacity for deep-sea exploration and research in every coastal area with deep ocean worldwide. From 200 to nearly 11,000 meters below sea level, the deep sea encompasses the single largest—and arguably the most critical—biosphere on Earth. Globally, two-thirds of all exclusive economic zones combined have water depths between 2,000 and 6,000 meters, making this a particularly critical depth range to access. This study includes information for 186 countries and territories, analyzed by subregional, regional, and income groups. The data were collected through both an online survey and manual research. We found that globally, 52% of respondents agreed that exploration and research were considered important in their community. A third of respondents agreed they had the in-country technology to conduct deep-sea exploration and research, and half agreed they had in-country deep-sea expertise. Survey results revealed that the most important challenges worldwide are funding, access to vessels, and human capacity. The top three global opportunities for deep-sea exploration and research were training opportunities, less expensive data collection technology, and better data access and analysis tools. This assessment provides the baseline information necessary to strategically develop, equitably implement, and quantitatively measure the impact of deep-sea exploration and research capacity development over the coming years. It is now possible to measure the evolution of deep-sea capacity over the next decade, an important indicator of progress during the UN Decade of Ocean Science for Sustainable Development.